Efektivitas Pengelolaan Labortarium IPA Pada SMP Negeri 1 Mambroko Kabupaten Sumba Tengah - Maimunah H. Daud; Nona Yanti Pratiwi (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the effectiveness of science laboratory management at SMP Negeri 1 Mamboro Central Sumba Regency. The management of IPA laboratory is restricted to laboratory facilities and infrastructures based on Permendiknas no. 24, 2007, science laboratory management at SMP Negeri 1 Mamaboro, and practicum activities in science laboratory at SMP Negeri 1 Mamboro.This research includes evaluative research with qualitative approach. The research subjects are science subjects, students of class VII and class VIII. The data were collected by observation, interview, questionnaire and documentation. The analysis used was descriptive analysis. The result of observation, interview and documentation analysis indicated that IPA laboratory facilities and infrastructures as supporting of IPA activities included in the appropriate category (S) have value of conformity with the overall standard of Permendiknas No. 24 of 2007 on facilities and infrastructure of IPA laboratory for 79. The results of interview analysis with science subject teachers and filling questionnaires by science subjects teachers on science laboratory management in SMP Negeri 1 Mamboro included in the appropriate category (S) with a value of 74.8. The results of the questionnaire analysis conducted by the students about the suitability of practicum activity showed the value of 66.8 and included in the appropriate category (S).